Complex analysis of financial state and performance of construction enterprises - Krivka, Algirdas; Stonkutė, Eglė (Business, Management and Economics Engineering, 2015)
The paper analyses the financial state and performance of large constructions enterprises by applying financial indicators. As there is no one single decisive financial indicator enabling to objectively assess enterprise performance, the multi-criteria decision making (MCDM) methods are applied with four groups of financial ratios (profitability, liquidity, solvency and asset turnover) acting as evaluation criteria, while the alternatives assessed are two enterprises compared throughout the reference period of three years, also with the average indicator values of the whole construction sector. The weights of the criteria have been estimated by involving competent experts with chi-square test employed to check the degree of agreement of expert estimates. The research methodology contributes to the issue of complex evaluation of enterprise financial state and performance, while the result of the multi-criteria assessment – the ranking of enterprises and sector average with respect to financial state and performance – could be considered worth attention from business owners, potential investors, customers or other possible stakeholders.